Design and optimization of Π-shaped slotted dual-band SIW antenna for 5G applications - Alam, Md Mahabub; Nurhafizah, Abu Talip Yusof; Yasmin, Abdul Wahab; Mohamad Shaiful, Abdul Karim; Rahman, Md. Suaibur (Arqii Publication, 2025)
This paper presents the design and optimization of a dual-band, linearly polarized Substrate-I ntegrated Waveguide (SIW) antenna for 5G base stations, addressing challenges such as increased path loss and interference at millimeter-wave (mm-wave) frequencies. The innovation lies in a Π-shaped slotted SIW structure, enabling wideband operation across the 28 GHz and 38 GHz bands. Two longitudinal slots and one transversal slot, etched on a Rogers 5880 substrate, are strategically optimized to achieve dual-band performance. The antenna achieves a bandwidth of 1.786 GHz (27.491 - 29.277 GHz) for the 28 GHz band and 683 MHz (37.496 - 38.179 GHz) for the 38 GHz band. Simulations conducted using Computer Simulation Technology (CST) Microwave Studio software indicate gains of 7.9 dB and 8.05 dB, beamwidths of 64.1° and 61.7°, and radiation efficiencies of 94.83% and 92.61% at 28 GHz and 38 GHz, respectively. To validate the design, an Artificial Neural Network (ANN) model was employed, achieving high predictive accuracy with R² values of 0.98 for resonance frequency and 0.972 for gain. Compared to prior works, the proposed antenna offers enhanced gain, efficiency, and bandwidth, making it a promising solution for mm-wave 5G applications.